2021
DOI: 10.3389/fmars.2021.749185
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Effect of Binary Typhoons on Ocean Surface Waves in Waters Surrounding Taiwan

Abstract: The ocean surface waves during Super Typhoons Maria (2018), Lekima (2019), and Meranti (2016) were reproduced using hybrid typhoon winds and a fully coupled wave-tide-circulation modeling system (SCHISM-WWM-III). The hindcasted significant wave heights are in good agreement with the along-track significant wave heights measured by the altimeters aboard the SARAL (Satellite with ARgos and ALtiKa) and Jason-2 satellites. Two numerical experiments pairing Super Typhoons Maria (2018) and Meranti (2016) and Super T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…As discussed in Part 1 (Xu et al., 2022), distance is a useful criterion in observational statistics to determine whether tropical cyclones are interacting. However, the critical distance is very different in different studies, ranging from 500 to 1600 km (Chang et al., 2021), as a result of the large differences in typhoon size and intensity. For example, the critical distance in E.‐J.…”
Section: Effects Of the Interactions Of Binary Typhoonsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in Part 1 (Xu et al., 2022), distance is a useful criterion in observational statistics to determine whether tropical cyclones are interacting. However, the critical distance is very different in different studies, ranging from 500 to 1600 km (Chang et al., 2021), as a result of the large differences in typhoon size and intensity. For example, the critical distance in E.‐J.…”
Section: Effects Of the Interactions Of Binary Typhoonsmentioning
confidence: 99%
“…Cha et al., 2021). As one tropical cyclone approaches a second, its track, intensity wave and the distribution of precipitation are all affected by their interactions (Brand, 1970; Carr & Elsberry, 1998; Carr et al., 1997; Chang et al., 2021; Dong & Neumann, 1983; Jang & Chun, 2015a; Yang et al., 2008). The interactions between multiple tropical cyclones and the environmental flow are highly complex and the accurate prediction of extreme rainfall events influenced by binary typhoons remains challenging (Jang & Chun, 2015b; Shin et al., 2006; Wu et al., 2003; Yang et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high efficiency, numerical robustness, and multipurpose applications, the SCHISM and SCHISMlike models have been successfully applied to investigate the fate and transport of fecal coliform contamination, and residence time in a tidal estuarine system [27,28], predict the extent of coastal flooding induced by a combination of storm surges and SLR [13,14,29], and assess the tidal current power at a small island [30]. The SCHISM is also an extendable mathematical model that is applicable for investigating the nonlinear interactions among tides, surges, waves, and currents when coupled with a wind-wave model [31][32][33][34][35][36][37].…”
Section: Two-dimensional Hydrodynamic Model and Its Configurationmentioning
confidence: 99%
“…However, a majority of these studies focused on the information from one or two real storms or only on modeling the surge heights along the coast. In addition, recent studies have shown the importance of relevant parameterization for wind forcing in simulating storm surge in the East Asia (Yu et al, 2019;Hsiao et al, 2020;Chang et al, 2021). For example, Hsiao et al (2020) and Chang et al (2021) applied temporally and spatially varying wind fields to improve the hindcast of storm surge.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have shown the importance of relevant parameterization for wind forcing in simulating storm surge in the East Asia (Yu et al, 2019;Hsiao et al, 2020;Chang et al, 2021). For example, Hsiao et al (2020) and Chang et al (2021) applied temporally and spatially varying wind fields to improve the hindcast of storm surge. Yu et al (2019) simulated the highest storm tide level for the past 122 storm surges in Taiwan, which not only generated a large surge database but also offered useful insights into the design and development of coastal flood protection infrastructure.…”
Section: Introductionmentioning
confidence: 99%